MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN METODE PEMBELAJARAN BERBASIS INKUIRI PADA MATA PELAJARAN AKIDAH AKHLAK DI MTS WIRDULLATIFAH NW BANJAR MANIS - Syafirin, Muhammad; Tarmizi Tahir, Muhammad (LP2M STAI Darul Kamal NW Kembang Kerang, 2021)
Abstract This research was conducted to improve student learning outcomes in Akidah Akhlak subjects on the material of repentance, obedience, istiqamah and sincerity using the direct instruction model in class VII/1 MTs Wirdullatifah NW Banjar Manis. This type of research is Classroom Action Research (CAR) through the application of inquiry-based learning methods. In practice, classroom action research using inquiry-based learning methods can improve student learning outcomes in learning Akidah Akhlak. This can be seen from the student learning outcomes, initially in the pre-cycle of 7 students there were only two students who completed (28.6%) with an average score of 66.85, the highest score was 80 and the lowest score was 50. From the pre-cycle after improvements were made in the first cycle of learning, there was an increase to 4 students who completed KBM, the average value was 73.28%, the highest score was 85 and the lowest score was 55. In the improvement of learning in the second cycle, 7 students completed KBM 100%, the average score was 83 ,57%, the highest score is 90 and the lowest score is 75.